Effect of the microalgae Chlorella vulgaris on the management of larvae and fry of Orestias luteus native to Lake Titicaca, Peru - Amaru Chambilla, Glicerio Reyes (2023)
The test was carried out in the month of March 2021 at the Continental Laboratory of Puno - IMARPE, in order to determine the effect of the use of the microalga Chlorella vulgaris as food at the beginning of the ontogeny of Orestias luteus, a test was carried out with 1600 larvae kept in two 45 L aquariums. One aquarium with Chlorella vulgaris (green water), and the other aquarium without Chlorella vulgaris (clear water). It is reflected that during the first 7 days the larvae fed and maintained with microalgae presented higher survival due to the high nutritional level that the microalgae presents, such as docosahexaenoic acid (DHA), apparently influenced the development of the Orestias Luteos larvae. Likewise, when added directly to the aquariums, the microalgae exerted a positive influence on the physiological state of Orestias luteus larvae, which translates into the obtaining of high-quality fingerlings.It is concluded that live food such as planktonic organisms constitute the feeding base in the larval stage of Carachi Amarillo and obtaining high survival of seeds allowing better growth and greater survival.